Anterior cruciate ligament reconstruction in 107 competitive wrestlers: outcomes, reoperations, and return to play at 6-year follow-up - Marigi, E. M.; Song B. M.; Wasserburger J. N.; Camp, C. L.; Levy, B. A.; Stuart, M. J.; Okoroha, K. R.; Krych, A. J. (Orthopaedic Journal of Sports Medicine, 2022)
Background: Wrestling is a physically demanding sport, with young athletes prone to anterior cruciate ligament (ACL) injuries. There is a paucity of data evaluating the results of ACL reconstruction (ACLR) in this cohort.